Ghrelin Gene Deletion Alters Pulsatile Growth Hormone Secretion in Adult Female Mice - Hassouna, Rim; Fernandez, Gimena; Lebrun, Nicolas; Fiquet, Oriane; Roelfsema, Ferdinand; Labarthe, Alexandra; Zizzari, Philippe; Tomasetto, Catherine; Epelbaum, Jacques; Viltart, Odile; Chauveau, Christophe; Perello, Mario; et al. (Frontiers in Endocrinology, 2021)
Using preproghrelin-deficient mice (Ghrl-/-), we previously observed that preproghrelin modulates pulsatile growth hormone (GH) secretion in post-pubertal male mice. However, the role of ghrelin and its derived peptides in the regulation of growth parameters or feeding in females is unknown. We measured pulsatile GH secretion, growth, metabolic parameters and feeding behavior in adult Ghrl-/- and Ghrl+/+ male and female mice. We also assessed GH release from pituitary explants and hypothalamic growth hormone-releasing hormone (GHRH) expression and immunoreactivity. Body weight and body fat mass, linear growth, spontaneous food intake and food intake following a 48-h fast, GH pituitary contents and GH release from pituitary explants ex vivo, fasting glucose and glucose tolerance were not different among adult Ghrl-/- and Ghrl+/+ male or female mice. In vivo, pulsatile GH secretion was decreased, while approximate entropy, that quantified orderliness of secretion, was increased in adult Ghrl-/- females only, defining more irregular GH pattern. The number of neurons immunoreactive for GHRH visualized in the hypothalamic arcuate nucleus was increased in adult Ghrl-/- females, as compared to Ghrl+/+ females, whereas the expression of GHRH was not different amongst groups. Thus, these results point to sex-specific effects of preproghrelin gene deletion on pulsatile GH secretion, but not feeding, growth or metabolic parameters, in adult mice.